PEMBUATAN DAN APLIKASI RIZOBAKTERI PEMACU TUMBUH TANAMAN UNTUK OPTIMALISASI LAHAN MARGINAL - Rosmini Rosmini; Sri Anjar Lasmini; Flora Pasaru; Hasriyanty Hasriyanty; Dance Tangkesalu (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Marginal land is land that is less fertile because it has a low content of nutrients and organic matter. To increase soil fertility can be done by giving fertilizers, in the form of inorganic fertilizers, organic fertilizers, and biofertilizers. One of the biofertilizers used in agriculture today is a group of rhizosphere bacteria or often known as Plant Growth Promotion Rhizobacteria (PGPR). Community service aims to assist farmers in developing Plant Growth Promotion Rhizobacteria (PGPR). The method applied is training and mentoring. The results of the implementation of community service showed that the participants (farmers) were enthusiastic about participating in each activity topic, this was shown by the activeness of the participants at various stages of the activity. The results of the evaluation of the knowledge, skills and attitudes of farmers through the answers on the questionnaire given to the material on the technology of making and applying PGPR indicated that the skills of farmers to make PGPR increased by 70% and farmers who intend to develop and apply PGPR as biological fertilizer on their farms amounted to 60%. Thus, the implementation of community service motivates farmers to develop PGPR as a biofertilizer so that it is expected to optimize the use of marginal land to increase agricultural production